Bioremediasi Tanah Terkontaminasi Hidrokarbon Menggunakan Teknik Bioaugmentasi - Radjali Amin; F. Madubun; D. Rahyuni (Universitas Lambung Mangkurat, 2020)
Among various bioremediation methods, bioaugmentation is the one which frequently used. In this study, bioaugmentation was conducted by utilising Pseudomonas aeruginosa, Bacillus cereus, and Brevibacterium flavum. Many studies on and implementations of this method have been conducted. However, this method still needed to be studied especially with reference to its implementations to small automotive workshops, which their number was increasing, as the sources of the soil contamination. The objective of this study was to identify the most effective bacteria in removing total hydrocarbon content (TPH) from contaminated soils and to understanding several characteristics of the method. Laboratory research was set up and the experimental design was complete randomised design (CRD) with three replications. Statistical test of Anova with α 5% was carried out to evaluate the results of the study. The treatments of this study were three species of bacteria which were inoculated separately into the contaminated soils. The parameters were TPH, pH and the density of bacteria consortiums. The highest effective removal of TPH was showed by P. aeruginosa, 64,1% (δ+2,61%), followed by B. flavum and B cereus. This treatment had pH dropped two points and the density of bacteria consortium increased 6-10 times. The main limitation of this study was the number of parameters which was a few resulting difficulties in understanding the hydrocarbon degradation processes. The results of this study may give significant contributions to managers of small automotive workshops in cities which currently are not managed their spills properly.